2020
DOI: 10.1177/1078155220971794
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ifosfamide induced encephalopathy in patients receiving concomitant fosaprepitant

Abstract: Introduction The incidence of Ifosfamide-induced encephalopathy (IIE) ranges from 5-30%. Aprepitant and fosaprepitant may increase the risk of IIE; however, data is limited. The objective of this study was to characterize the incidence of IIE in patients receiving concomitant fosaprepitant. Methods This single-center, retrospective chart review included adult patients diagnosed with sarcoma who received at least one administration of high dose ifosfamide (≥1800mg/m2) and fosaprepitant between January 2017 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We chose to continue ifosfamide with thiamine prophylaxis. In another study, the rate of recurrence of IIE was reported as 26.3% in whom ifosfamide were re-administered in subsequent courses 19…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We chose to continue ifosfamide with thiamine prophylaxis. In another study, the rate of recurrence of IIE was reported as 26.3% in whom ifosfamide were re-administered in subsequent courses 19…”
Section: Discussionmentioning
confidence: 95%
“…In another study, the rate of recurrence of IIE was reported as 26.3% in whom ifosfamide were re-administered in subsequent courses. 19 In conclusion, ifosfamide is an important chemotherapeutic agent used in treatment of many malignant tumors. Children with cancer are exposed to many factors likely to disturb the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Ifosfamide-Induced Encephalopathy (IIE) berkisar antara 5-30% dari semua pasien yang menerima infus ifosfamid. Gejala yang dilaporkan jenis IIE bervariasi, dari kantuk ringan atau pusing, hingga halusinasi, kejang, koma, dan bahkan kematian (Modi dan Cimino, 2021). Penelitian Hingmire dan Raut insiden Chemotherapy-Induced Nausea and Vomiting (CINV) bervariasi dari 30% sampai >90% dalam 24 jam setelah pemberian pertaman kemoterapi emetogenik sedang (carboplatin, cisplatin, doxorubicin, epirubisin, ifosfamid, irinotecan atau metotreksat) serta sangat emetogenik tanpa profilaksis antiemetik (Hingmire dan Raut, 2015).…”
Section: Efek Samping Kemoterapiunclassified